Akuntansi Syariah dan Akuntansi Konvensional: Komparasi Nyata Dari Tinjauan Literature - Kamaruddin Kamaruddin; Saparuddin Siregar (Jurnal Ilmiah Ekonomi Islam, 2022)
Comparison between sharia and conventional accounting is still a debate, especially at the practical and philosophical levels. This study uses a review of the literature to emphasize the differences between Islamic accounting and conventional accounting. The rapid growth of the Islamic finance industry causes conventional accounting practices to be insufficient to accommodate its unique characteristics. So from an examination of the literature, Islamic society clearly needs an accounting system that is in accordance with the ideology and values of Muslims. The findings of this study clearly describe the differences between Islamic accounting and conventional accounting, both in terms of philosophy and in practice. Thus strengthening the position of Islamic accounting as a science that is historically earlier than conventional accounting. Other findings from this study help break the obsession with the notion that Islamic accounting adopts conventional accounting.